Dubai transient city. Anatomy of a post-urban phenomenon - Tiziano Aglieri Rinella (Agathón)
In the global imaginary, Dubai is a fascinating and dynamic young metropolis projected to the future. Many urban planning proposals attempted to control its rapid expansion, boosted by oil discovery in 1966. John Harris, George Candilis, the Milan-based BBPR, Reima Pietilä and in more recent times Norman Foster, OMA and others presented proposals quickly outdated by its bursting urban development. Nowadays, the glittering lights of this city’s skyline quickly sprouted from the desert, advertise the daring image of a city in which reality and fiction are often merged. But what is concealed behind this amazing urban spectacle? Its very fast and uncontainable growth has generated massive phenomena of urban sprawl and proliferation of junk spaces. Hi-density zones are alternated to vast desert unbuilt areas, in a fragmented urban landscape that generates, in many European expats, a diffused estranging ‘uncanny’ feeling. In a city Non-City, where malls and hotels become the main social gathering centres, the urban structure is similar more to a dis-connection of Non-Places, elevated to the rank of urban landmarks. Shall Dubai demonstrate skills of resilience and urban regeneration, facing the nowadays fast and unpredictable transformations of the economic and geopolitical scenarios of the Gulf region? The essay aims to investigate the dynamics that led to the current dystopian scenario of the nowadays urban landscape of Dubai, proposing possible solutions to relieve the impact of the existing contradictions.